Optimizing Returns: A Holistic Financial Model for Off-Grid Glamping Ventures (Global Journal of Management and Business Research, 2024)
Glamping is becoming increasingly popular and may yield better financial returns than traditional hotel developments in some situations especially in unspoiled locations which are inaccessible for traditional hotel resort construction because it disturbs the site too much This paper presents a detailed financial model for analysing the performance of glamping properties to inform decision-making about investing in them It focuses particularly on properties that are off the beaten track for singles couples small families and others who want to unwind and commune with nature in relatively isolated off-grid locations such as nature reserves vineyard wineries golf resorts or wellness and spa hideaways In the authors view glamping is particularly well suited to this kind of hotel In the normal way the financial model summarizes the development of these properties in detail and itemizes the specific capital investments needed to establish an off-grid glamping property in contrast to a similar traditional grid-connected hotel
Keywords: glamping; business case analysis; new hotel development